Numerical study of novel OME1−6 combustion mechanism and spray combustion at changed ambient environments - Wiesmann, Frederik; Han, Dong; Qiu, Zeyan; Strauß, Lukas; Rieß, Sebastian; Wensing, Michael; Lauer, Thomas (Frontiers of Energy, 2024)
For a climate-neutral future mobility, the so-called e-fuels can play an essential part. Especially, oxygenated e-fuels containing oxygen in their chemical formula have the additional potential to burn with significantly lower soot levels. In particular, polyoxymethylene dimethyl ethers or oxymethylene ethers (PODEs or OMEs) do not contain carbon-carbon bonds, prohibiting the production of soot precursors like acetylene (C2H2). These properties make OMEs a highly interesting candidate for future climate-neutral compression-ignition engines. However, to fully leverage their potential, the auto-ignition process, flame propagation, and mixing regimes of the combustion need to be understood. To achieve this, efficient oxidation mechanisms suitable for computational fluid dynamics (CFD) calculations must be developed and validated. The present work aims to highlight the improvements made by developing an adapted oxidation mechanism for OME1−6 and introducing it into a validated spray combustion CFD model for OMEs. The simulations were conducted for single- and multi-injection patterns, changing ambient temperatures, and oxygen contents. The results were validated against high-pressure and high-temperature constant-pressure chamber experiments. OH*-chemiluminescence measurements accomplished the characterization of the auto-ignition process. Both experiments and simulations were conducted for two different injectors. Significant improvements concerning the prediction of the ignition delay time were accomplished while also retaining an excellent agreement for the flame lift-off length. The spatial zones of high-temperature reaction activity were also affected by the adaption of the reaction kinetics. They showed a greater tendency to form OH* radicals within the center of the spray in accordance with the experiments.<br
Keywords: oxygenated fuels; reaction kinetics; oxidation mechanisms; computational fluid dynamics (CFD); oxymethylene ethers (OME); e-fuels; multi-injection; spray-combustion